2022
DOI: 10.3390/diagnostics12122968
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio with Osteoporosis: A Meta-Analysis

Abstract: Osteoporosis is characterized by low bone mass and increased bone fragility. Numerous studies have suggested that inflammation contributes to its pathogenesis. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are simple, noninvasive biomarkers that can reflect the inflammation status on human body. However, evidence on their associations with osteoporosis remains scant. The PubMed, Embase, and Cochrane Library databases were searched for relevant studies from their inception to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…These findings also suggest that SIRI values may serve as a tool for evaluating the risk of OPFs. Consistent with prior research ( 42 , 48 , 49 ), the present study demonstrated that a strong inflammatory response is detrimental to the prognosis of individuals with OP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings also suggest that SIRI values may serve as a tool for evaluating the risk of OPFs. Consistent with prior research ( 42 , 48 , 49 ), the present study demonstrated that a strong inflammatory response is detrimental to the prognosis of individuals with OP.…”
Section: Discussionsupporting
confidence: 92%
“…Inflammatory mechanisms underlying OP have also been proposed in recent years ( 40 , 41 ). It is evident that inflammation alters bone homeostasis, resulting in reduced bone mass, weaker bone strength, and decreased bone density, as well as ultimately a decrease in bone turnover, all of which contribute to adverse outcomes in OPFs ( 42 , 43 ). Increased circulating levels of pro-inflammatory cytokines and immune cells directly or indirectly affect bone turnover through various pathways ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the projected global increase in hip fracture, addressing the substantial hip fracture-associated health risks of older adults is crucial (1). Numerous studies have identi ed a positive association between postoperative mortality and various in ammatory parameters related to hip fracture surgery, including RDW (11,(16)(17)(18)(19), NLR (6,11,16,20,21), PLR (16, 21-23), C-reactive protein level (24), albumin level (25), and total lymphocyte count (25). To date, no prospective study has compared single laboratory parameters as prognostic factors for the mortality risk associated with hip fracture.…”
Section: Discussionmentioning
confidence: 99%